Effect of Sn on the energy storage performance and electric conduction mechanisms of BCZT ceramic. (2022) - Belkhadir, S.; Khardazi, S.; Mezzane, D.; Amjoud, M.; Shapovalova, O.; Laguta, V.; Raevski, I.; Pushkarova, K.; Lukyanchuk, I.; El Marssi, M.
Abstract: The B-site-doping method of barium titanate (BaTiO3 ) is one of the promising route to prepare lead-free materials with enhanced dielectric and piezoelectric properties. Lead-free (Ba0.85 Ca0.15 )(Zr0.1-x Snx Ti0.9 )O3 [BCZT:Sn] (x = 0, 0.02, 0.04 and 0.06) ceramics were synthesized using the sol-gel method. The effects of Sn content on the energy-storage performance and electric conduction mechanisms of BCZT ceramic were systematically investigated. The energy storage performance investigation showed that the recoverable energy storage has been enhanced with Sn doping rate, the composition doped x = 0.02 (BCZT: 2Sn) depicted the highest recoverable energy density and efficiency (Wrec = 19 mJ/cm 3, ɳ = 81.65%). The electrical properties of the BCZT:Sn ceramics were investigated using the impedance spectroscopy technique at temperature range of 25–450 °C. The net impedance of the samples showed a significant enhancement as the Sn content increases, owing to the lattice distortion created by the relative difference in the radius of Sn 4+ and Zr 4+ and different outer electronic shells. The AC conductivity was measured and analyzed as a function of frequency and temperature. Obtained activation energy values were associated with possible conduction mechanisms.